Use of phonolite and potassium-solubilizing bacteria in bean crops (Research, Society and Development, 2022)
The objective of this study was to analyze the use of phonolite rock powder associated with inoculation with potassium solubilizing bacteria (BSK) in bean crops. The experiment was carried out in pots until flowering time using a randomized block design in a factorial scheme 5 (3 doses of phonolite, KCl treatment and control) x 4 (three BSK strains and control treatment). Shoot dry matter (MSPA) and root dry matter (MSR), number of nodules (NN) and residual K in the soil were evaluated. The treatments that used the phonolite did not differ in plant development, but they were superior when compared to the control treatment. In the interaction doses of phonolite and inoculation, the strain UNIFENAS 100-94 stood out at doses 50% and 100% similar to the treatment in which KCl was used. Inoculation promoted greater plant development and residual K content in the soil.